PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA OUTSOURCING DI TINJAU DARI UNDANG-UNDANG NOMOR 6 TAHUN 2023 TENTANG PENETAPAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NOMOR 2 TAHUN 2022 TENTANG CIPTA KERJA MENJADI UNDANG-UNDANG (STUDI KASUS PT. VALDO SUMBER DAYA MANDIRI) - Gunandi, Jefri; Sulistiyantoro, Hariyo (Gapenas Publisher, 2023)
Enactment of Law Number 6 of 2023 concerning Determination of Regulations Government Replaces Law Number 2 of 2022 concerning Job Creation Becoming law brings several changes in the field of employment. One of the main points of this research is the protection of rights outsourced workers. In practice, the implementation of the Job Creation Law at PT. Valdo Sumber Daya Mandiri (PT. Valdo) is not running well. This is visible from the practice of unilateral termination of employment (PHK) of workers outsourcing that is not in accordance with the law, as well as discrimination not to work and not get a salary. This research uses the method normative juridical research with a statutory and regulatory approach case. Based on the research results, efforts are needed to improve legal protection for outsourced workers, especially at PT. Valdo. These efforts can be made through more socialization and law enforcement take firm action against violations that occur